Factors Affecting Phage–Bacteria Coevolution Dynamics - Ghadeer Jdeed; Bogdana Kravchuk; Nina V. Tikunova (Viruses)
Bacteriophages (phages) have coevolved with their bacterial hosts for billions of years. With the rise of antibiotic resistance, the significance of using phages in therapy is increasing. Investigating the dynamics of phage evolution can provide valuable insights for pre-adapting phages to more challenging clones of their hosts that may arise during treatment. Two primary models describe interactions in phage–bacteria systems: arms race dynamics and fluctuating selection dynamics. Numerous factors influence which dynamics dominate the interactions between a phage and its host. These dynamics, in turn, affect the coexistence of phages and bacteria, ultimately determining which organism will adapt more effectively to the other, and whether a stable state will be reached. In this review, we summarize key findings from research on phage–bacteria coevolution, focusing on the different concepts that can describe these interactions, the factors that may contribute to the prevalence of one model over others, and the effects of various dynamics on both phages and bacteria.